2007
DOI: 10.2116/analsci.23.1409
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Simultaneous Determination of Uric Acid and Ascorbic Acid on a Dynamically Modified Poly(dimethylsiloxane) Microchip

Abstract: Poly(dimethylsiloxane) microfluidic channels alternately modified by poly(diallyldimethylammonium chloride) and poly(sodium 4-styrenesulfonate) were successfully used to separate uric acid and ascorbic acid. Results show that uric acid and ascorbic acid can be well separated and detected simultaneously in modified microchips coupled with in-channel electrochemical detection. Under the optimal conditions, the linear ranges of uric acid and ascorbic acid were both from 25 to 600 μM, with the correlation coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 38 publications
0
23
1
1
Order By: Relevance
“…2, the EOF is more stable against any pH alteration on a modified microchannel other than on a native one. By comparing of the alteration of the EOF values, depending on the pH with reported similar methods [20][21][22][23] ( Table 1), we could find that there was only 0.06 of ΔEOF during a pH change from 8.0 to 11.0, which is the smallest one. Noticeably, there are at least one of two main aspects of difference between our research and those reports.…”
Section: Controlled Eof On a Modified Microchannelmentioning
confidence: 72%
See 1 more Smart Citation
“…2, the EOF is more stable against any pH alteration on a modified microchannel other than on a native one. By comparing of the alteration of the EOF values, depending on the pH with reported similar methods [20][21][22][23] ( Table 1), we could find that there was only 0.06 of ΔEOF during a pH change from 8.0 to 11.0, which is the smallest one. Noticeably, there are at least one of two main aspects of difference between our research and those reports.…”
Section: Controlled Eof On a Modified Microchannelmentioning
confidence: 72%
“…Qiu et al 21 reported a poly(diallyldimethylammonium chloride) (PDDA)/poly(sodium-p-styrenesulfonate) (PSS) modified PDMS chip to obtain a stable EOF based on reduced non-specific adsorption. In addition, a PDDA/nano-TiO2 coated microchip and a PDDA/nano-SiO2 coated microchip have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several other PDMS hydrophilic surface modification strategies have been explored, such as UV treatment [21,22], chemical vapor deposition [23], layer-by-layer (LBL) deposition [24,25], sol-gel coatings [26], silanization [27], dynamic modification with surfactants [28], and protein adsorption [29], but all result in the formation of what can be seen as a bilayer system unstable over time.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the wettability of PDMS surfaces has been improved by using methods such as plasma treatment, [3][4][5][6] UV treatment, 7,8 chemical vapor deposition, [9][10][11] layer-by-layer ͑LBL͒ deposition, [12][13][14] sol-gel coatings, 15,16 silanization, 17,18 dynamic modification with surfactants, [19][20][21][22] and protein adsorption. [23][24][25] In addition, combinations of UV or plasma treatment with chemical methods such as silanization, [26][27][28] graft polymerization, [29][30][31][32][33][34] and LBL methods 35,36 have been explored.…”
Section: Introductionmentioning
confidence: 99%